(3GdJfGaSjI GdbWGYjI (B:s (3OQGSI JMdjdjI dbWGY GdUfGYGJ GdZPGFjI (B/s - (3QRhb, GHJSGe s ((3GdLRGFQ (B: s (3OGQ GdCLjGd GdQbej(B, s, 2023)
(3jgOa gPG GdcJGH Edi YQV hJMdjd Cge GdeQJcRGJ GdfXQjI dJbjje GdJfGaSjI YGeI hGdJfGaSjI GdbWGYjI Ydi hLg GdNUhU(B. (3ceG jbOe GdcJGH OQGSI JWHjbjI dbWGY GdUfGYGJ GdZPGFjI aj GdLRGFQ ef NdGd bjGS Objb deDTQGJ JfGaSjI GdbWGY Ydi GdeSJhjjf GdeMdj hGdOhdj NdGd aJQI YTQ SfhGJ Hjf SfJj (B2008 (3h (B2018 (3ef NdGd SJ eDTQGJ(B.(3ceG Je dJMdjd Sdhc GdbWGY GdeOQhS YHQ YTQjf SfI Hjf SfJj (B2000 (3h (B2019 (3HGSJNOGe WQjbI GdJMdjd GdYGedj HGSJNOGe HQfGeL GdJMdjd GdGMUGFj (Bpss. (3jgOa JMOjO Cge GdeMOOGJ GdeJMceI aj JfGaSjI bWGY GdUfGYGJ GdZPGFjI GdLRGFQj hcPG CgejJg aj GdEbJUGO GdhWfj(B.s
(3eQGLY U(B.318-336s
Keywords: (3GdCZPjI GdUfGYjIs; (3GdefGaSIs